2017
DOI: 10.1080/03019233.2017.1294357
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic effects created by argon stirring liquid steel in a one-strand tundish

Abstract: Continuous casting of steel ensures the flexible production of different grades of slabs intended for the Rolling Mill departments. Therefore, it seems justifiable to search new solutions for tundish metallurgy. This study puts forward a new gas-permeable barrier's design solution with two circular porous plugs, whose purpose is to punctually agitate the liquid steel in tundish. Two argon injection system locations were tested. The results for the hydrodynamic pattern of liquid steel and bubbles' behaviour in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, the upward bubbly flow could homogenize the thermal field [10] and improve the flow characteristics [11,12] in the tundish. Cwudzinski [13] reported that gas bubbling located next to the stopper rod shows the best performance on flow control, with a 27% drop in dead volume. Chattopadhyay et al [14] carried out water modeling to investigate slag behaviors in a four-strand tundish using gas injection from the ladle shroud.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the upward bubbly flow could homogenize the thermal field [10] and improve the flow characteristics [11,12] in the tundish. Cwudzinski [13] reported that gas bubbling located next to the stopper rod shows the best performance on flow control, with a 27% drop in dead volume. Chattopadhyay et al [14] carried out water modeling to investigate slag behaviors in a four-strand tundish using gas injection from the ladle shroud.…”
Section: Introductionmentioning
confidence: 99%